Implementation of numerical modeling algorithms to examine the filtration of multiphase flow through the gas hydrate stability zone in the Ross Sea - Alekseeva, Natalia; Popov, Sergey; Poveshchenko, Yury; Podryga, Viktoriia; Kazakevich, Grigory; Chuvilin, Evgeny; Coffin, Richard (Environmental Research Communications, 2025)
In the Ross Sea region (Antarctica), evidence of warming, ice melt, and high levels of thermogenic gas hydrates indicate that deep-seated hydrocarbons contribute significantly to carbon cycles. The study investigates structural changes in the gas hydrate stability zone as methane moves from the hydrate-free zone to the seabed. A numerical fluid dynamics model is used to study the potential contribution of deep-seated carbon to the Ross Sea ice shelf, taking into account local thermodynamic equilibrium. The results of the calculation support the phenomenon of free gas from deep sediments that filtrates upward through the zone with methane hydrate stability conditions, partially converting into hydrate, while the remaining gas is capable of migrating higher into the water column. The process is accompanied by the formation of a three-phase (gas, hydrate, H 2 O) hydrate equilibrium zone, replacing the initially two-phase (hydrate, H 2 O) gas hydrate stability zone. The modeling results explain the discrepancy between the radiocarbon dating of the core and the study of the history of the ice sheet in the region.